Analysis of the Coupling Between Rectangular Microstrip Patches on Uniaxial Anisotropic Substrates DOI: 10.14209/jcis.1995.4 - R. S. Oliveira, J.; G. d’Assunção, A.; S. da Rocha, C. (Journal of Communication and Information Systems, 2015)
The effect of the dielectric anisotropy in the behavior of the resonant frequencies of coupled microstrip patches is investigated. In the analysis, the Hertz vector potentials technique, in the spectral domain, is used to determine the field components expressions, while the moment (Galerkin) method is used to solve the matrix equation obtained by imposing the boundary conditions of the structure under consideration. The microstrip patches substrates are composed by two uniaxial anisotropic dielectric materials. The optical axes in these dielectric layers are oriented perpendicularly to the ground plane. Numerical results are presented for the resonant frequency for the geometry under consideration. Excellent agreement was observed with results available in the literature for coupled microstrip patches on isotropic substrates.